Non-adherence to ART medication regimens among people living with HIV, who are registered with Leratong hospital in Gauteng province, South Africa - Moiloa, Edwin Mohlalefi (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: The study sought to establish the causes of non-adherence to ART medication regimens among people living with HIV. The research was conducted at Leratong Hospital in Johannesburg, Gauteng province, South Africa. The researcher selected a qualitative design in which 24 patients on ART and six healthcare providers in the field of HIV/AIDS, who fulfilled inclusion criteria of 18 and above years, were interviewed. Tape-recorded interviews as an instrument of data collection was used and patient-participants were approached and requested to participate in one to one interview as they came to collect their medication. Health personnel were approached in their respective offices and asked to be interviewed. Thematic Content Analysis (TCA) was later used to generate themes. The results indicated that adherence levels among the patients were sub optimal (less than 95%). Social economic related factors such as poverty, stigma and fear of disclosure; and medication side effects profoundly influenced adherence. Patient-related factors such as lack of social support, preference of traditional medicines, feeling better, substance abuse; and one health system-related factor being staff shortages, had a little contribution to poor medication adherence. According to the study findings, the process of ART delivery at the clinic had no contribution to patients‟ non-compliance. In fact it was found to have been intended at providing extrinsic motivation to, and raising the levels of adherence among the patients. When the patients stated their views concerning the programme, the major problem lay with strict time rules and that gave birth to forgetfulness. Their suggestion directed not to the health centers, but sorely to the government and all stakeholders including the ARV drugs-manufacturers, was that ART be provided in the form of three to six months injection. The findings revealed that stigma exacerbates non-adherence, so, there is a need to intensify health education campaigns against stigma in communities, workplaces and households. The findings from this study showed a significant relationship between treatment adherence and gender, in which women are generally more compliant than men to ART, so it was recommended that men be given extra pre-ARV counseling and compliance checking.